EVALUASI GEOMETRI PELEDAKAN OVERBURDEN UNTUK MENDAPATKAN FRAGMENTASI IDEAL DI PT. TAMBANG RAYA USAHA iTAMA (TRUST) KUTIM, KALIMANTAN TIMUR - Muhamad Darmawan; Raimon Kopa M.T (Journals Mining Engineering : Bina Tambang, 2022)
Abstract. Coal Mining PT. Tambang Raya Usaha Tama (TRUST) with an open-pit mining system. In alternative pit 3 there are 100 cm chunks or boulder with a percentage of +40%. While the target for fragmentation in the company is 20%. So the boulders resulting from the blasting process will disrupt the loading of the overburden. The value of digging time on the Hitachi PC 2500 Excavator that is too long will certainly cause the productivity of the digging tool to be disrupted. The average digging time of the Hitachi PC 2500 Excavator Excavator on the material resulting from blasting from the actual blasting activity is ±15 seconds (CTM). This digging time is still far from the standard digging time set by the company, which is in the range of 10 – 12 seconds. The research method was carried out with a blasting geometry design based on the R L Ash, Konya, and ICI Explosive methods. The results of the analysis of the fragmentation distribution using the R.L.Ash method with a fragmentation distribution of 100 cm in size retained 5% with a powder factor of 0.56 kg/bcm. The C.J Konya method with a fragmentation distribution of 100 cm in size retained 8% with a powder factor of 0.50 kg/bcm. The Ici Explosive method with a fragmentation distribution of 100 cm in size retained 7% with a powder factor of 0.40 kg/bcm. based on the results of consultations with the distribution company, the fragmentation size of 100 cm was retained 19% with a powder factor of 0.28 kg/bcm. Of all these methods, the optimal method for blasting geometry is to obtain a fragmentation distribution that suits the company's needs, namely the blasting geometry based on the results of consultations with the company. This can be seen from the results of the powder factor which is not too large and also the rock fragmentation obtained in accordance with the company's target.